Visceral Leishmaniasis or Systemic Lupus Erythematosus Flare? - Sunny Garg; Mousumi Kundu; Amit Nandan Dhar Dwivedi; Lalit Prashant Meena; Neeraj Varyani; Asif Iqbal; Kamlakar Tripathi (Case Reports in Immunology)
Systemic lupus erythematosus (SLE) is a multisystem disorder characterised by B-cell hyperactivity with production of multiple autoantibodies. Fever in SLE may be caused by disease exacerbation or by infection. We report a patient of SLE that was later complicated by fever, pancytopenia, and massive splenomegaly. Corticosteroid therapy for SLE might have masked the underlying infection at earlier stage. Despite negative results of rk-39 test and bone marrow biopsy, a very high suspicion for visceral leishmaniasis (VL) led us to go for direct agglutination test (DAT) and polymerase chain reaction (PCR) for leishmanial antigen that revealed positive results. Moreover, significant improvement in clinical and biochemical parameters was noted on starting the patient on antileishmanial therapy.